Synthesis and Characterization of Cu-Co Substituted Strontium Hexaferrite for Magnetic Applications - Burcu ERTUG (Medžiagotyra)
In this study, the structural and magnetic characterizations of a series of SrCoxCuxFe12-2xO19; 0.0 ≤ x ≤ 0.5 samples, which were produced by the conventional ceramic method, were carried out. The structure was examined by X-ray diffraction (XRD) technique and optical microscopy. A vibrating sample magnetometer (VSM) was used to characterize the ferrimagnetic properties. XRD patterns confirmed the presence of a single phase as Sr-hexaferrite while there were not any peaks of unreacted Fe2O3 phase. The densities varied between 92 – 98 %. XRD patterns of the Sr-hexaferrite samples were slightly modified because of the co-substitution of Cu-Co; however, the magnetic properties changed remarkably. The sample with Cu-Co of x = 0.1 content had the highest saturation magnetization (33.52 emu/g), remanence (19.74 emu/g), and coercivity (4.3 kOe). The synthesized magnetic samples were found to be suitable for the development of attractive ferrimagnetic properties for the current ferrite magnets.